Maternal precarity and HPA axis functioning shape infant gut microbiota and HPA axis development in humans. - Johanna R Jahnke (Public Library of Science (PLoS), 2021)
Background Early life exposure to adverse environments, and maternal stress in particular, has been shown to increase risk for metabolic diseases and neurobehavioral disorders. While many studies have examined the hypothalamic-pituitary-adrenal axis (HPA axis) as the primary mechanism behind these relationships, emerging research on the brain-gut axis suggests that the microbiome may play a role. In this study, we tested the relationships among maternal precarity and HPA axis dysregulation during the peripartum period, infant gut microbiome composition, and infant HPA axis functioning. Methods Data come from 25 mother-infant dyads in the Galápagos, Ecuador. Women completed surveys on precarity measures (food insecurity, low social support, depression, and stress) and gave salivary cortisol samples during and after pregnancy. Infant salivary cortisol and stool were collected in the postpartum. Statistical significance of differences in microbial diversity and relative abundance were assessed with respect to adjusted linear regression models. Results Maternal precarity was associated with lower diversity and higher relative abundance of Enterobacteriaceae and Streptococcaceae and a lower relative abundance of Bifidobacterium and Lachnospiraceae. These patterns of colonization for Enterobacteriaceae and Bifidobacterium mirrored those found in infants with HPA axis dysregulation. Maternal HPA axis dysregulation during pregnancy was also associated with a greater relative abundance of Veillonella. Conclusions Overall, exposures to precarity and HPA axis dysregulation were associated with an increase in groups that include potentially pathogenic bacteria, including Enterobacteriaceae, Streptococcaceae, and Veillonella, and a decrease in potentially protective bacteria, including Bifidobacterium and Lachnospiraceae, as well as a decrease in overall diversity.